Output gaps and cyclical indicators: Finnish evidence - Harri Pönkä; Mikko Sariola (Bank of Finland, 2021)
The output gap is a commonly used tool to assess the state of the business cycle, and as such, a key input for policy makers. In this article, we employ principal components analysis (PCA) to derive an estimate of the output gap in Finland that summarizes the information of widely used cyclical indicators. This methodology produces an output gap that is similar to the ones obtained from the main methods used at the Bank of Finland and the European Commission, but requiring considerably less modelling effort. The method is also flexible and can readily be adopted to internalize additional information that captures special circumstances, such as the current pandemic. In this spirit, we extend our information set to include a service turnover indicator, and find that it clearly improves the method's ability to capture the exceptional downturn in 2020.
urn:nbn:fi:bof-202110012043
Keywords: E32; C38; 330; cyclical indicators; output gap; potential output; principal component analysis; service turnover; COVID-19